PENGARUH PARTISIPASI PENGUSAHA MUSLIM BUGIS TERHADAP PENGENTASAN KEMISKINAN DI KABUPATEN BONE SULAWESI SELATAN - Syamsul Bahri (Islamic Banking and Finance, 2021)
The purpose of this study was to determine how much influence participation (X) had on poverty alleviation (Y), in Bone Regency, South Sulawesi. This research is included in the explanatory research. It is said so, because this study connects 2 (two) variables, namely participation as the independent variable (X), and poverty alleviation as the dependent variable (Y). Furthermore, to determine the effect of participation (X) of Bugis Muslim entrepreneurs in Bone Regency, hypothesis testing was carried out by comparing the t table with t arithmetic (t test and F test). Based on the results of the study, it is known that the effect of participation on poverty alleviation is obtained by a tcount of3.516with a significance of 0.001. Thus, participation (X) has a significant effect on poverty alleviation (Y). Keywords: Participation, Bugis Muslim Entrepreneurs, Poverty